Spinning into butter - Twain, Norman; Pitt, Lou; Howe, Ryan; Atchison, Doug; Brokaw, Mark; Richardson, Miranda; Bridges, Beau; Parker, Sarah Jessica; Williamson, Mykelti; Gilman, Rebecca Claire (Screen Media Films, 2009)
A vicious hate crime at an elite New England college thrusts the new dean of students into the investigation. When charged with maintaining order on campus, she is forced to examine her own feelings about race. Based on the critically acclaimed play, a compelling movie that examines the emotional fallout of prejudice within the cloistered walls of academia.